2019
DOI: 10.1111/anae.14940
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomised controlled trial of the management of systolic blood pressure during endovascular thrombectomy for acute ischaemic stroke

Abstract: Summary It is unknown whether systolic blood pressure augmentation during endovascular thrombectomy improves clinical outcomes. This pilot randomised controlled trial aimed to assess the feasibility of differential systolic blood pressure targeting during endovascular thrombectomy procedures for anterior circulation ischaemic stroke. Fifty‐one eligible patients fulfilling the national criteria for endovascular thrombectomy were randomly assigned to receive either standard or augmented systolic blood pressure m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
(46 reference statements)
2
22
0
Order By: Relevance
“…This trial randomly assigned 51 patients to receive either standard or augmented systolic blood pressure management from the start of anaesthesia to recanalisation of the target vessel. 106 There were no safety concerns with trial procedures and all feasibility targets were achieved.…”
Section: In Patients With Acute Ischaemic Stroke Caused By Large Vessel Occlusion and Undergoing Mechanical Thrombectomy (With Or Withoutmentioning
confidence: 99%
“…This trial randomly assigned 51 patients to receive either standard or augmented systolic blood pressure management from the start of anaesthesia to recanalisation of the target vessel. 106 There were no safety concerns with trial procedures and all feasibility targets were achieved.…”
Section: In Patients With Acute Ischaemic Stroke Caused By Large Vessel Occlusion and Undergoing Mechanical Thrombectomy (With Or Withoutmentioning
confidence: 99%
“…The currently ongoing MAS-TERSTROKE study, assesing two hemodynamic targets during EVT from the beginning of anesthesia to the moment of recanalisation, might provide an interesting perspective. The pilot trial showed no differences in early neurological improvement, all-cause mortality at 90 days, intraoperative complications or intracerebral haemorrhage rates between patients in two BP target groups (130-150 mmHg and 160-180 mmHg) [54].…”
Section: Type Of Reperfusion Therapymentioning
confidence: 87%
“…In light of the shortcomings of previous work, the study published in this month's issue of Anaesthesia by Deng et al. is an important first step in refining intra‐operative thrombectomy practice. The authors conducted a pilot study to assess the feasibility of a future larger randomised controlled trial.…”
Section: Advantages and Disadvantages Of General Anaesthesia (Includimentioning
confidence: 99%